(De)Humanising People in Discussions around Race and Religion - Lea Skewes (Kvinder, Køn & Forskning)
Welcome to our conversation about the complex entanglements of racialization and Islamophobia in Denmark. The following panel discussion was part of a Gendering in Research seminar which took place the 26th of May 2023 at Aarhus University. We invited three speakers from three different disciplines to offer their take on how race, or rather racialization, and religion intersect in different Danish contexts. Coming from the field of Educational Psychology Associate Professor Iram Khawaja from Danish School of Education spoke about Muslimness as a racialized category. In her talk she offered examples from her interview data about how religion and race intersect in Denmark, especially in the educational system where discourses contrasting religiosity and secularity govern. Professor Lene Kühle from the Department of the Study of Religion at the School of Culture and Society offered a talk entitled Is the regulation of religious individuals and communities in Denmark discriminatory or racist? As the title indicate she offered a more judicial take on how we navigate religion in a Danish context. And finally, we had Professor Christian Suhr from the Department of Anthropology at the School of Culture and Society offer the talk Muslims, Muslims, Muslims: flimflam about Muslims in Europe. Suhr’s talk was based on his experiences as a film maker, and he drew attention to how the framing of movies about minorities (like Muslims) shape our understandings of what it means to belong to a particular minority. So, this is where our conversation starts - welcome.